PHYSICAL TRAINING IN GROWING A HEALTHY GENERATION AND SPORTS REQUIREMENTS - Yusupov Akmaljon AbdugopporovichYusupov Akmaljon Abdugopporovich (International Journal of Innovations in Engineering Research and Technology, 2021)
In this article, the structure of human organs and their functional maturity. Internal organs, nerves and movement, musculoskeletal system, control of body harmony and their functional activity